Accounting of value of ecosystem services in the desert: an example of the Kubuqi Desert ecosystem - Liu, Yanbing; Kong, Lingqiao; Jiang, Chaoqiang; Zhang, Xiaoling; Ouyang, Zhiyun (Frontiers in Earth Science, 2024)
Ecological products and ecosystem services are essential for human survival and development. Gross Ecosystem Product (GEP) is a method to combine the value of ecosystem services and can reflect the status of ecosystem and ecological conservation and restoration performance. The conservation and restoration of desert ecosystems play an important role in expanding global cultivated land, ensuring food security, and improving human wellbeing. However, ecosystem services and the value of GEP in deserts have been neglected. Taking the Kubuqi Desert ecosystem as an example, this study evaluated the pattens, GEP value, and its change in the Kubuqi Desert ecosystem from 2000 to 2020. Our study found that 1) over the past 20 years, the areas of wetlands, forests, grasslands, and shrubs in the Kubuqi desert ecosystem had increased by 100.65%, 6.05%, 2.24%, and 2.03%, respectively, while that of desert had decreased by 10.62%; 2) the GEP of Kubuqi in 2020 was 55.48 billion CNY, among which its sandstorm prevention value was the highest (39.39%); 3) The value of ecosystem services in the Kubuqi desert ecosystem were all increased over the 20-year period and the largest increase came from sandstorm prevention (increased by 195.09%). This study emphasizes how GEP accounting can promote desert conservation and restoration, quantifies the contribution of desert ecosystems to human wellbeing, and provides future GEP accounting suggestions for desert ecosystems. This study can provide scientific information on the conservation and restoration of global desert ecosystems.